Artificial selection reveals the role of transcriptional constraints in the maintenance of life history variation. Issue 3 (7th April 2020) - Pick, Joel L.; Hatakeyama, Masaomi; Ihle, Kate E.; Gasparini, Julien; Haussy, Claudy; Ishishita, Satoshi; Matsuda, Yoichi; Yoshimura, Takashi; Kanaoka, Masahiro M.; Shimizu‐Inatsugi, Rie; Shimizu, Kentaro K.; Tschirren, Barbara
Abstract: The trade‐off between reproduction and self‐maintenance is a cornerstone of life history theory, yet its proximate underpinnings are elusive. Here, we used an artificial selection approach to create replicated lines of Japanese quail ( Coturnix japonica ) that differ genetically in their reproductive investment. Whole transcriptome sequencing revealed that females from lines selected for high reproductive output show a consistent upregulation of genes associated with reproduction but a simultaneous downregulation of immune genes. Concordant phenotypic differences in immune function (i.e., specific antibody response against keyhole limpet hemocyanin) were observed between the selection lines, even in males who do not provide parental care. Our findings demonstrate the key role of obligate transcriptional constraints in the maintenance of life history variation. These constraints set fundamental limits to productivity and health in natural and domestic animal populations.